Prognostic Enigma of Pancreatic Solid Pseudopapillary Neoplasm: A Single-Center Experience of 63 Patients - Wang, Xinbo; Zhu, Daojun; Bao, Wei; Li, Min; Wang, Sizhen; Shen, Rongxi (Frontiers in Surgery, 2021)
Backgrounds: Studies investigating prognostic factors of solid pseudopapillary neoplasm (SPN) have been published with conflicting findings. Methods: Retrospective analysis of 63 consecutive cases of SPN in our institution from January 2010 to December 2019 was carried out. The clinicopathological features, treatment practices along with survival associations were collected and analyzed. Results: Fifteen patients (23.8%) were male, and 48 (76.2%) were female, with a mean age of 34.0±14.5 years. The larger tumor size was correlated with the more mixed components (p = 0.000) and the higher Ki-67 index (p = 0.042). No recurrence was found in the 9 patients whose tumors fulfilled the WHO criteria for malignancy due to the presence of at least perineural invasion (6.4%), angiovascular invasion (2.3%), and/or adjacent organ invasion (6.4%). Microscopic infiltrative growth was detected in 9 (14.3%) tumors, which was correlated significantly with the WHO criteria (p = 0.002), capsule invasion (p = 0.005) and pancreatic parenchyma invasion (p=0.001), but not with disease-free survival (p = 0.13). CD99 was found to be positively expressed in 88.9% (40/45) of tumors, and more likely to have depressed Ki-67 index (p = 0.016). After median follow-up of 58 months, only 2 patients (3.2%) had a recurrence after their first operation outside of our hospital. No patient died due to tumor progression. Conclusions: Although survival is favorable with aggressive surgery, it is generally difficult to assess the malignant potential of pancreatic SPN. Future investigations into the role of pathologic evaluation will unveil the surgical enigma.